The Use of Subscribed Online Databases among the Postgraduates at the University of Malaya Library - Sinnasamy, J.; Mohamad, P. (2007)
This paper describes the steps taken by the University of Malaya Library to successfully implement the continual improvement project for the year 2005, entitled “Promoting the Use of Online Databases”. It includes the efforts by the library to increase the usage of online databases among the postgraduates by 20% as compared to the year 2004. It is realized that increasing the basic awareness of these online databases among the library users and highlighting the relevant databases for the respective faculty prove to be vital to bring about an increase in the usage. This paper will be helpful to libraries trying to increase the usage of online databases subscription so as to make the subscription cost effective